2007
DOI: 10.1126/science.1143578
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Wnt Signaling in a Mammalian Model of Accelerated Aging

Abstract: The contribution of stem and progenitor cell dysfunction and depletion in normal aging remains incompletely understood. We explored this concept in the Klotho mouse model of accelerated aging. Analysis of various tissues and organs from young Klotho mice revealed a decrease in stem cell number and an increase in progenitor cell senescence. Because klotho is a secreted protein, we postulated that klotho might interact with other soluble mediators of stem cells. We found that klotho bound to various Wnt family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
589
3
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 688 publications
(637 citation statements)
references
References 22 publications
29
589
3
16
Order By: Relevance
“…Several studies demonstrated a critical role for residues within klotho's putative active site in mediating some of the activities of klotho. Thus, mutations of these residues abolished its effect on TRPV5 and on the renal phosphate transporter NaPi-2a (11,32,33), but did not affect its ability to inhibit Wnt signaling (34). Our studies indicate that these amino acids are not required for klotho tumor suppressor activity.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Several studies demonstrated a critical role for residues within klotho's putative active site in mediating some of the activities of klotho. Thus, mutations of these residues abolished its effect on TRPV5 and on the renal phosphate transporter NaPi-2a (11,32,33), but did not affect its ability to inhibit Wnt signaling (34). Our studies indicate that these amino acids are not required for klotho tumor suppressor activity.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, it was demonstrated that KL1 is essential and sufficient to mediate the antiinflammatory activity of klotho in senescent cells, whereas KL2 did not show any such activity (35). Similarly, KL1 is mandatory and sufficient to inhibit Wnt signaling by klotho, whereas KL2 is devoid of this activity (34). Our data suggest that klotho tumor suppressor activities are KL1 dependent and that KL2 by itself cannot significantly inhibit proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Parathyroid hormone (PTH) induces 25-hydroxyvitamin D 3 1a-hydroxylase (1-OH) to generate 1,25VD. (7) Klotho binds to various proteins, including TRPCs, WNT, and receptors for VEGF, FGF, TGF-b, and IGF, (8)(9)(10)(11)(12)(13)(14) to elicit a wide variety of biological responses, including inhibition of fibrosis, epithelial-mesenchymal transition and cancer metastasis, and modulation of endothelial function and insulin action, as well as calcium-phosphate metabolism.…”
Section: Introductionmentioning
confidence: 99%